Família: peça fundamental na ressocialização de adolescentes em conflito com a lei? - Santos, Fernanda Valéria Gomes dos (2007)
Teenagers in conflict with, before law, and their families social vulnerability have been largelly discussion matter in academic, political and social scenery. It has also become usual debating teenagers aggravating envolvement in infringing pratices, society s stigmatizing view on about teenagers and recurrences vertiginous number increase. In front of before this reality, this study accademic wok aims at treating working questions that are pertinent to teenager in conflict ressocialization ant it his work is meant undertansing comprehensing domestic dynamic contribution in the resocialization process and in this process aintenance support in teenagers who have commited perpretateb inflictng acts. This research participants consited of two groups: on one side, ten profissionals among psychologists, social advisers, guiderd social assistants attendants and pedagogues that work act in assted freedom measure and teenagers families that had received assisted freedom measure progression. The tools data collection have been compounded by semdirected interview and with a questionaire, elaborated by this researcher, from this investigation objetives. Methodology nature is a a qualitative one, considering that this kind of methodology permits, allows a contextual phenomenons description. The data analyses denoted that teenagers in conflict with law resocialization several facets are vitalized in a certain reality that is permeat by precariousness not only in economic field, but also with regard to bonds trodden on the violence, on the precariousness and on the instability that are flitted by psychosocial aspects such as stimatization and guiltness culpabilization. In front of these aspects, it seems that family s revolt constitutes inconformity demonstration expression, in front of their existence condtions and received treataments these factores cohexistence, among other-ones in creased of family, domestic peolpe difficulty in dealing with their childrensons and daughters in dealing with psychoactive substances and involvement with friends that exercive pernicous influence upon them see to support, to strenghten teenager s maintenance in the transgressive world. When family members, however, give support, uphold, effectively, their children yuong sons and daughters on well accepted behaviours well breeding, edcating them, these demostrate changing wish retaking their studies including professional, vocational couses, and swerving themselves from these friends group tho could contribute returnig to transgressive practices.